Clinical course and risk factors of mortality in Mycobacterium avium complex lung disease without initial treatment. (September 2020) - Wang, Ping-Huai; Pan, Sheng-Wei; Shu, Chin-Chung; Chen, Chung-Yu; Wei, Yu-Feng; Cheng, Shih-Lung; Wang, Hao-Chien; Yu, Chong-Jen
Abstract: Purpose: Mycobacterium avium complex-lung disease (MAC-LD) is increasing worldwide and may progress to cause mortality significantly. However, for patients without initial treatment at diagnosis, the survival outcomes and predictors of mortality remain unclear. Methods: From 2011 to 2017, MAC-LD patients at two medical centers in Taiwan were screened, and those who received MAC treatment at the initial were excluded. The clinical course and characteristics were recorded. Cox regression analysis and receiver operating characteristic (ROC) curves were performed to assess risk factors of mortality within 4 years. Results: We included 123 MAC-LD patients without initial MAC treatment. The mean follow-up period was 4.15 ± 2.52 years. Twenty-two (17.9%) patients died within four years. Multivariate analysis showed that four independent factors related to 4-year mortality were consolidation pattern (hazard ratio [HR] 6.0, 95% confidence interval [2.3–15.5]), radiographic score > 6 (HR:11.0 [4.0–31.1]), radiographic deterioration within two years (HR: 5.2 [2.1–13.1]) and no MAC treatment during follow up (HR: 6.5 [1.3–31.1]). The areas under the ROC curves for prediction of 4-year mortality for the combination of consolidation and radiographic score >6, the two factors plus radiographic progression, the two plus no MAC treatment, and the combination of the four factors were 0.702, 0.798, 0.758, and 0.835, respectively. Conclusions: The four-year mortality rate in MAC-LD without initial treatment is high. Presence of consolidation pattern and radiographic score >6 at initial visit, radiographic deterioration and no treatment during follow-up were risk factors of 4-year mortality in initially untreated MAC-LD. Highlights: Four-year mortality rate is notable in those without initial MAC treatment. Consolidation and radiographic score initially are risk factors for mortality. Radiographic deterioration within two years is associated with four-year mortality. No timely treatment and the above three factors together are highly risky for mortality.